Polypoid arteriovenous malformation of the rectum: A case report - Krizzuk, Dimitri; Cotesta, Maria; Galiffa, Giampaolo; Peluso, Ilaria; Falbo, Francesco; Biancucci, Andrea; Puscio, Sara; Michelotto, Chiara; Pasecinic, Carolina; Montalto, Gioacchino Maria; Sammartino, Francesco (Frontiers in Surgery, 2022)
Background: Intestinal arteriovenous malformation is an abnormal connection between arteries and veins that bypasses the capillary system and may be a cause of significant lower gastrointestinal bleeding. On endoscopy, arteriovenous malformations are usually flat or elevated, bright red lesions. Overall, rectal localization of arteriovenous malformations is rare. The same may be said about polypoid shape arteriovenous malformations. Herein, we present a case of a large rectal polypoid arteriovenous malformations. Methods: Clinical, diagnostic, and treatment modalities of the patient were reviewed. Pre- and post-operative parameters were collected and analyzed. The clinical English literature is also reviewed and discussed Results: A 60-year-old female patient was admitted to our emergency department for rectorrhagia and anemia. Rectoscopy revealed a polypoid lesion in the rectum and the biopsy showed fibrosis, necrosis areas, and hyperplastic glands. A total body contrast-enhanced computed tomography (CT) was performed revealing a parietal pseudonodular thickening with concentric growth and contrast enhancement, extending for about 53 mm. The mass wasn’t removed endoscopically due to concentric growth, sessile implant, and submucosal nature. The patient underwent an uneventful laparoscopic anterior rectal resection. The postoperative hospitalization was free of complications. Histology showed the presence of a polypoid AVM composed of dilated arteries, veins, capillaries, and lymphatics, engaging the submucosa, muscularis, and subserosa layer. Conclusion: After a review of the current English literature, we found only one case of rectal polypoid AVM. The scarcity of documented cases encumbers optimal diagnostic and treatment approaches.